Effective Strategies to Ensure Teachers’ Psychological Well-Being Amid Social Crisis: A Lesson from COVID-19 Pandemic - Abdullah, Muhammad Yahya; Putri, Shalsabilla Rinira (Muslim Education Review, 2025)
In the context of a crisis such as the Covid-19 pandemic, the decline in teachers’ psychological well-being has become a serious issue that affects the effectiveness of the learning process. Through previous literature studies, this research aims to map various strategies that can foster teachers’ psychological well-being in a social crisis, using the COVID-19 pandemic as the model crisis. This can serve as a guide for regulators in educational institutions in facing future crisis events. The research method used is a systematic literature review, which allows researchers to systematically evaluate and synthesize findings from various relevant literature sources published between 2019 and 2023, including only journal articles. Eventually, the results identified 10 strategies that can be implemented: teacher creativity, resource support, supportive environment, relational support, teacher competency development, psychological support, organization, physical training, collaboration with policy makers, and additional funding. It is hoped that these strategies can become the basis to contribute positively to teachers’ psychological well-being while facing complex challenges in times of crisis such as the COVID-19 pandemic later.